2008
DOI: 10.1163/156856208785540163
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin promotes proliferation and matrix production of intervertebral disc cells cultured in three-dimensional poly(lactic-co-glycolic acid) scaffold

Abstract: Previously, we have proven that fibrin and poly(lactic-co-glycolic acid) (PLGA) scaffolds facilitate cell proliferation, matrix production and early chondrogenesis of rabbit articular chondrocytes in in vitro and in vivo experiments. In this study, we evaluated the potential of fibrin/PLGA scaffold for intervertebral disc (IVD) tissue engineering using annulus fibrosus (AF) and nucleus pulposus (NP) cells in relation to potential clinical application. PLGA scaffolds were soaked in cells-fibrin suspension and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…Material Publication Annulus Fibrosus Enhanced with genipin Likhitpanichkul et al, 2014;Likhitpanichkul et al, 2015;Long et al, 2016a;Schek et al, 2011 Nucleus Pulposus Combined with hyaluronic acid Li et al, 2014;Park et al, 2012 3D Culture Combined with poly(lactic-co-glycolic acid) Sha'ban et al, 2008;Stern et al, 2000;Stich et al, 2015 Correia et al, 2013). It has yet to be shown whether Gellan gum could withstand compressive forces in long-term IVD repair experiments.…”
Section: Locationmentioning
confidence: 99%
“…Material Publication Annulus Fibrosus Enhanced with genipin Likhitpanichkul et al, 2014;Likhitpanichkul et al, 2015;Long et al, 2016a;Schek et al, 2011 Nucleus Pulposus Combined with hyaluronic acid Li et al, 2014;Park et al, 2012 3D Culture Combined with poly(lactic-co-glycolic acid) Sha'ban et al, 2008;Stern et al, 2000;Stich et al, 2015 Correia et al, 2013). It has yet to be shown whether Gellan gum could withstand compressive forces in long-term IVD repair experiments.…”
Section: Locationmentioning
confidence: 99%
“…The increased mechanical resistance of the scaffolds for application in intervertebral discs is made possible by the use of composites. 2,5,48,57 Meniscus. The meniscus has a semilunar shape and extends over the upper tibial surface, improving its congruence with the femoral condyles.…”
Section: Scaffolds: Physical and Substrate Porous Supports For Seedinmentioning
confidence: 99%
“…Fibrin possesses chemically active gelling property, which typically occurs during blood coagulation in addition to the advantages described previously. Several studies investigating fibrinbased hybrid scaffold demonstrated its potential for the promotion of homogeneous cell distribution and cartilaginous tissue formation (33)(34)(35). PNIPAAm was also used for this purpose, and it possessed the merit of a synthetic thermoresponsive polymer for tissue engineering with versatile manipulation of its chemical structure and molecular weight as well as easy conjugation with other components.…”
Section: Ecm-based Scaffoldsmentioning
confidence: 99%